The intersubjective endeavor of psychopathology research: methodological reflections on a second-person perspective approach - Galbusera, Laura; Fellin, Lisa Chiara (Frontiers in psychology, 2014)
Research in psychopathology may be considered as an intersubjective endeavor mainly concerned with understanding other minds. Thus, the way we conceive of social understanding influences how we do research in psychology in the first place. In this paper, we focus on psychopathology research as a paradigmatic case for this methodological issue, since the relation between the researcher and the object of study is characterized by a major component of "otherness". We critically review different methodologies in psychopathology research, highlighting their relation to different social cognition theories (the third-, first- and second-person approaches). Hence we outline the methodological implications arising from each theoretical stance. Firstly, we critically discuss the dominant paradigm in psychopathology research, based on the Diagnostic and Statistical Manual of Mental Disorders (DSM, American Psychiatric Association, 2013) and on quantitative methodology, as an example of a third person methodology. Secondly, we contrast this mainstream view with phenomenological psychopathology which - by rejecting the reductionist view exclusively focused on behavioural symptoms - takes consciousness as its main object of study: it therefore attempts to grasp patients’ first person experience. But how can we speak about a first person perspective in psychopathology if the problem at stake is the experience of the other? How is it possible to understand the experience from “within”, if the person who is having this experience is another? By addressing these issues, we critically explore the feasibility and usefulness of a second person methodology in psychopathology research. Notwithstanding the importance of methodological pluralism, we argue that a second person perspective should inform the epistemology and methods of research in psychopathology, as it